Assessment of the Causal Effects of Obstructive Sleep Apnea on Atrial Fibrillation: A Mendelian Randomization Study - Li, Yalan; Leng, Yiming; Tang, Haibo; Deng, Peizhi; Wang, Jie; Yuan, Hong; Miao, Rujia; Mu, Ping (Frontiers in Cardiovascular Medicine, 2022)
Background Obstructive sleep apnea (OSA) and atrial fibrillation (AF) are epidemiologically correlated, but the causal relationship between them remains elusive. We aimed to explore the causal relationships between the OSA and AF. Method Using both Finnish biobank and publicly available genome-wide association study data (GWAS), we conducted a two-sample Mendelian randomization (MR) analysis to estimate the causal effect of OSA on AF, both in the primary analysis and replicated analysis. The inverse variance weighted MR was selected as the main method. To further test the independent causal effect of OSA on AF, we also performed multivariable MR (MVMR), adjusting for body mass index (BMI), hypertension, and coronary artery disease (CAD), respectively. Results In the primary analysis, OSA was significantly associated with increased risk of AF (OR 1.21, 95% CI 1.11-1.32) and the replicated analysis showed consistent results (OR 1.17, 95% CI 1.05-1.30). Besides, there was no heterogeneity and horizontal pleiotropy observed both in the primary and replicated analysis. Further multivariable MR suggested that the causal relationships between OSA and AF exist independently of BMI and coronary heart disease. The MVMR result after adjustment for hypertension is similar in magnitude and direction to the univariate MR. But it did not support a causal relationship between OSA and AF. Conclusion Our study found that genetically driven OSA causally promotes AF. This causal relationship sheds new light on taking effective measures to prevent and treat OSA to reduce the risk of AF. Key words: obstructive sleep apnea; atrial fibrillation; Mendelian Randomization; causal inference; instrumental variable (IV)